PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KOMITMEN AFEKTIF STUDI PEGAWAI BALAI BESAR KULIT KARET DAN PLASTIK UMBULHARJO YOGYAKARTA - Asyifa puja wida Nurmeisya; Prayekti Prayekti (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the influence of Transformational Leadership Style, Work Motivation, and Work Discipline on Affective Commitment, both partially and simultaneously. This research is a quantitative research, as the population in this study are all employees, with a total sample of 62. The sampling technique uses purposive sampling technique. The data analysis technique uses multiple linear regression which is equipped with data tests, assumption tests, T tests and F tests. The results of this study indicate that the Transformational Leadership Style variable has a significant effect on Affective Commitment, as evidenced by the results of the T test, namely the value of Tcount>Ttable or significant < 0.05 with a value of 2.280 > 1.671 or 0.026 < 0.05. Then the variable Work Motivation has a significant effect on Affective Commitment, as evidenced by the results of the T test, namely the value obtained, namely Tcount>Ttable or significantly <0.05 with a value of 2,703> 1,671 or 0.009 <0.05. And the Work Discipline variable does not significantly influence Affective Commitment, as evidenced by the results of the T test, namely the value obtained is Tcount <Ttable or significant > 0.05 with a value of 1.557 <1.671 or 0.120 > 0.05. Simultaneously, Transformational Leadership Style, Work Motivation, and Work Discipline have an effect on Affective Commitment with ɑ = 0.05.